2015
DOI: 10.2147/ijn.s78167
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent and time-dependent effects of hyperthermia mediated by dextran-coated La0.7Sr0.3MnO3: in vitro studies

Abstract: Background The purpose of this study was to investigate the therapeutic efficacy of dextran-coated (Dex) La 0.7 Sr 0.3 MnO 3 (LSMO) nanoparticles-mediated hyperthermia at different temperatures (43°C, 45°C, and 47°C) based on cell killing potential and induction of heat shock proteins in a murine melanoma cell (B16F1) line. Methods LSMO nanoparticles were synthesized by a citrate-gel method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
4
9
0
Order By: Relevance
“…Haghniaz et al showed a minimum temperature of 45°C was required to decrease the viability of the melanoma cell line B16F [1]. Our study obtained consistent results by using temperatures lower than 45°C and showed these temperatures failed to eliminate B16 cells.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Haghniaz et al showed a minimum temperature of 45°C was required to decrease the viability of the melanoma cell line B16F [1]. Our study obtained consistent results by using temperatures lower than 45°C and showed these temperatures failed to eliminate B16 cells.…”
Section: Discussionsupporting
confidence: 85%
“…Hyperthermia is a procedure by which the temperature of a specific body part or the whole organism is elevated above the standard physiological temperature [ 1 ]. A temperature range of 42°C to 45°C is used therapeutically as a single agent or as an adjuvant to radiotherapy, chemotherapy or immunotherapy in the cancer treatment [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the vasculature however appeared dependent on ultrasound pressure but largely invariant over the heating times studied. Several studies have confirmed time-dependent cellular effect using various in vivo and in vitro models but these have made use of USMB to perturb the vasculature in advance [37] [38].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, HT range between 39–45°C has demonstrated enhanced blood flow followed by improved tissue oxygenation causing direct or indirect cell death leading vascular deterioration [44] [45]. The mode of cell death induced by HT is known to be time-and temperature-dependent [46] [37] [47]. Usually, temperature up to 47°C results in apoptotic cell death while increasing the temperature above 50°C exhibits necrosis as a result of tumour cells destruction [36].…”
Section: Discussionmentioning
confidence: 99%
“…While the acute or moderate HS can be managed physiologically by the endogenous defense systems, severe and/or continuous heat stress, accompanied by over-expression of certain heat shock proteins, overburdens the physiological maneuvers leading to ineffective defense, organ damage, and lethality (Dehbi et al 2010). For example, repeated cycles of hyperthermia were shown to dramatically increase HSP production when compared to a single, acute HS, resulting in enhanced apoptosis (Haghniaz et al 2015). Prolonged exposure to heat stress has been shown to increase the production of reactive oxygen species (ROS) in skeletal muscle (Azad et al 2010) that can enhance various deleterious consequences such as protein modifications, proteolysis, autophagy, and inflammation and affect skeletal muscle physiology (Montilla et al 2014;Dodd et al 2010;McClung et al 2010;Whidden et al 2010).…”
Section: Introductionmentioning
confidence: 99%